The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.5694/j.1326-5377.2007.tb01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐care testing of capillary glucose in the exclusion and diagnosis of diabetes in remote Australia

Abstract: Objectives: To determine the utility of point‐of‐care (POC) capillary blood glucose measurements in the diagnosis and exclusion of diabetes in usual practice in primary health care in remote areas. Design: Cross‐sectional study comparing POC capillary glucose results with corresponding venous glucose levels measured in a reference laboratory. Participants: 200 participants aged 16–65 years enrolled: 198 had POC capillary glucose measurements; 164 also had acceptable venous glucose laboratory results. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…However, in a recent report, Ritchie et al emphasized the utility of modern POC-glucose testing for screening purposes in a high-risk rural population [10], confirming previous evidence from epidemiological studies in remote areas [9], and the general population [11]. This data, as well as our evidence that shows that state-of-the-art POC-glucose technology can be used reliably as a diagnostic tool as well, demonstrates that the evolving technology of POC-glucose testing can offer many advantages beyond glucose monitoring.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, in a recent report, Ritchie et al emphasized the utility of modern POC-glucose testing for screening purposes in a high-risk rural population [10], confirming previous evidence from epidemiological studies in remote areas [9], and the general population [11]. This data, as well as our evidence that shows that state-of-the-art POC-glucose technology can be used reliably as a diagnostic tool as well, demonstrates that the evolving technology of POC-glucose testing can offer many advantages beyond glucose monitoring.…”
Section: Discussionsupporting
confidence: 58%
“…However, despite many obvious advantages (low sample volume, short turnaround time, and availability outside of the laboratory) and ongoing improvements in analytical performance, there is limited evidence on the possible use of POC glucose testing for diagnostic purposes, and results collected so far remained controversial [68]. Although some evidence from epidemiological studies suggest that POC glucose meters could be helpful in screening for diabetes, particularly in remote areas [911], their use in the diagnosis of diabetes is not recommended, due to both insufficient precision and accuracy and the inherent, sample-dependent flaw of results [13]. Namely, whole blood glucose, as measured by POC glucose meters, is approximately 11% lower than plasma glucose, but the difference is hematocrit dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies have analyzed the utility of POC capillary glucose as a diagnostic test with varied results (1416). Two of these studies specifically examined the utility of POC testing among high-risk populations (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Two of these studies specifically examined the utility of POC testing among high-risk populations (15,16). One study in the Australian indigenous population (15) found that POC glucose had good discriminatory capacity for predicting undiagnosed diabetes (using fasting venous glucose as the standard), and the other study in Maori (16) found that POC glucose had acceptable discriminatory capacity (using OGTT as the gold standard). The differing levels of discrimination achieved may reflect diabetes presenting as fasting hyperglycemia compared with diabetes presenting as postprandial hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation